MANIFESTASI WUJUD DAN MAKNA PRAGMATIK KEFATISAN BERBAHASA DALAM RANAH PENDIDIKAN - Rahardi, R. Kunjana (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
This research on phatic communion is aimed at describing the forms and the pragmatic meanings of phatic language in Indonesian society, especially in the educational domain. Based on its pragmatic meanings, the utterance in the educational domain can be categorized into five pragmatic meanings, namely (a) phatic function in utterances of acceptance, (b) phatic function in the form of utterances of rejection, (c) phatic function in the form of utterances of invitation, (d) phatic function in the form of utterances of thanking, and  (e) phatic function in the form of utterance of greeting.